An exploration of patient satisfaction with and experience of a sexual abuse survivors clinic. (February 2022) - Birdi, Gurkiran; Caswell, Rachel J; Ross, Jonathan DC; Pattison, Helen; Ayinde, Oluseyi; Lorimer, Karen
Background: The scale and extent of sexual violence perpetrated in the United Kingdom is being increasingly acknowledged. Support after the initial disclosure is often sought in NHS sexual health clinics. The purpose of this service evaluation was to explore patient satisfaction and experience amongst sexual health clinic attendees who disclosed sexual violence and were subsequently managed in a specialist sexual abuse survivors clinic. Methods: Semi-structured interviews were conducted with ten service users and interview transcripts were analysed using interpretative phenomenological analysis (IPA) to assess users' experiences within the clinic. Results: Participants were all female (aged 18–54 years) and had experienced sexual violence between 2 weeks and 15 years prior to interview, and the majority self-identified as White British (6/10). IPA analysis revealed three distinct overarching themes which were important to this group of patients when evaluating their care: delivery of care in the context of judgement and stigma, aspects of care identified as healing or harmful to recovery, and the importance of the processes of providing care. Conclusion: Understanding the experiences of sexual violence survivors in healthcare settings can optimise the provision of patient-oriented care and support. This includes ensuring the service user is in control of the consultation, the risks of re-traumatisation are minimised, and individuals receive relevant and accurate information but in a manageable volume and format.